2016
DOI: 10.3906/biy-1507-121
|View full text |Cite
|
Sign up to set email alerts
|

Identification and cloning of highly epitopic regions of Clostridium novyi alpha toxin

Abstract: Introduction Clostridium novyi causes gangrene in humans and animals. Among the various toxins produced by this pathogen (Hatheway, 1990), alpha toxin has a molecular weight of approximately 200-250 kDa and enzymatic activity on Rho receptors in mammalian cells, which cause vascular permeability and cell rounding in culture (Bette et al., 1991). Homology studies have shown that alpha toxin belongs to the large clostridial cytotoxin family (Hofmann et al., 1995). This family comprises glycosyltransferase by mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The alignment of our selected fragment, ATXF (1822-1992 aa), with the highly antigenic C-terminal segment of ATX, specifically pNTF12 (1800-1958 aa), further supports the rationale behind our immunoinformatic design. According to research by Busch et al and Gord-Noshahri et al (Busch et al, 2000; Gord-Noshahri et al, 2016), pNTF12 is identified as a hydrophilic surface protein responsible for receptor binding activity. It exhibits high mobility and lacks catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The alignment of our selected fragment, ATXF (1822-1992 aa), with the highly antigenic C-terminal segment of ATX, specifically pNTF12 (1800-1958 aa), further supports the rationale behind our immunoinformatic design. According to research by Busch et al and Gord-Noshahri et al (Busch et al, 2000; Gord-Noshahri et al, 2016), pNTF12 is identified as a hydrophilic surface protein responsible for receptor binding activity. It exhibits high mobility and lacks catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium novyi is the causative organism for gangrene in humans and animals (Gord-Noshahri et al, 2016). Based on the production of different toxins, C. novyi is categorized into 4 types (A-D) (Oakley et al, 1947, 1959; Willis & others, 1964).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, several experimental recombinant vaccines of C. novyi alpha toxin have been prepared and evaluated using immunological methods. Results have shown that antibody produced against recombinant proteins was more effective than that of normal toxin (Daryaei et al 2017 ; Noshahri et al 2016 ).…”
Section: Vaccine Productionmentioning
confidence: 99%